2021
DOI: 10.1101/2021.12.10.21267607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High correlation between binding IgG (anti-RBD/S) and neutralizing antibodies against SARS-CoV-2 six months after vaccination

Abstract: Vaccination is considered the most important measure to control the COVID-19 pandemic. Extensive follow-up studies with distinct vaccines and populations are able to promote robust and reliable data to better understand the effectiveness of this pharmacologic strategy. In this sense, we present data regarding binding and neutralizing antibodies throughout time, from vaccinated and previously infected (PI) health care workers (HCW) in Portugal. We analyzed serum samples of 132 HCW, vaccinated and with previous … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
(32 reference statements)
3
6
1
Order By: Relevance
“…Although previous studies have shown good correlation between the Anti-RBD antibodies and virus neutralization (13,14), present study shows a different picture as almost all the participants had Anti-RBD antibodies, but only 69% had neutralizing titre. Anti-RBD antibody levels were significantly higher among participants that had neutralizing antibodies compared to participants who didn't.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Although previous studies have shown good correlation between the Anti-RBD antibodies and virus neutralization (13,14), present study shows a different picture as almost all the participants had Anti-RBD antibodies, but only 69% had neutralizing titre. Anti-RBD antibody levels were significantly higher among participants that had neutralizing antibodies compared to participants who didn't.…”
Section: Discussioncontrasting
confidence: 92%
“…Our finding is in agreement with the other previous studies. (14,15) Also neutralizing titre and anti-RBD antibody titre were significantly higher among the health care workers, which might be due to repeated exposure of SARS-CoV2 among them. Participants who had history of contact with COVID-19 positive participants had significantly higher anti-RBD antibodies.…”
Section: Discussionmentioning
confidence: 95%
“…However, others have shown that binding and neutralizing antibody titers are thought to be correlated with each other (10-14). Specifically, the anti-s RBD IgG assay used here has been highly correlated with neutralizing antibodies elicited by vaccination strengthening our use of this quantitative measure of immunity in our cohort (12).…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies demonstrated that high titers of anti-RBD antibodies and NAbs were induced in vaccinated individuals [ 7 , 8 , 9 ]. A high correlation between RBD binding antibodies and NAbs was revealed [ 25 ]. Therefore, some health care settings and private health services use anti-RBD IgG levels to predict vaccine effectiveness in vaccinated individuals.…”
Section: Discussionmentioning
confidence: 99%